CUSTOM, IMMIGRATION AND QUARANTINE (CIQ) DALAM MENDUKUNG PENYELENGGARAAN EVENT WISATA BISNIS/MICE DI INDONESIA: Tinjauan terhadap Tindakan Karantina Tumbuhan untuk Kebutuhan Pameran - Wardhani, Annisa; Rudatin, Christina L.; Setyawan , Heri; Anggraini, Asterina (Warta Pariwisata, 2025)
The Business Tourism Industry or better known as MICE (Meeting, Incentive, Convention and Exhibition) is considered significant in driving the national economy. According to data from the Indonesian Ministry of Tourism and Creative Economy in 2023, the contribution of the MICE sector to the national tourism industry is around 30 (thirty) percent. Not only developing in organizing international meetings/conferences such as the G20 Summit or ASEAN SUMMIT, the organization of international exhibitions in Indonesia is also growing significantly. Government support for increasing the organization of international exhibitions is given in the form of policies that encourage the smooth implementation of exhibition activities, one of which is the policy related to CIQ (Custom, Immigration and Quarantine) which can make it easier for tourists/goods/animals/exhibition plants to enter and leave Indonesia. This study will focus on analyzing plant quarantine measures in organizing exhibition activities where the purpose of these plants is as exhibition goods/participated as participants/exhibitors in plant exhibitions. Sending plants from abroad into Indonesia for exhibition purposes requires specific and detailed procedures administratively and technically operationally. The methods used in this study are observation, interviews and literature studies. The output of this study is a systematic and comprehensive description of quarantine procedures and actions on plants intended for exhibition purposes.